Analisis Strategi Promosi Hotel Mandarin Oriental Jakarta Post Pandemi Covid – 19 - Nicko Gana Saputra; Reni Sulistiyowati; Gavriel Kevin Wijaya (Jurnal Sains Terapan Pariwisata, 2021)
Promotion Strategy is a plan for optimal use of promotional elements: advertising, public relations, personal selling and sales promotion. (Lamb, Hair, McDaniel, 2001). Because of that, the promotion strategy of a hotel is very decisive so that the hotel can survive all conditions and existing competition. In the initial observations, it appears that the promotional elements mentioned above are not in ideal conditions or do not take place as expected. To describe and explain the Promotional Strategy of Mandarin Oriental Hotel Jakarta in terms of Advertising, Sales Promotion, Personal Selling, Direct Marketing and Public Relations. This research is a research with a qualitative approach, using a case study technique, which is an empirical study that investigates phenomena in their context, in real life, especially when the boundaries and context are not clear. Data collection by interview, observation and documentation. Data analysis techniques by means of reduction, display, and verification. Data Validation Techniques by means of Triangulation. Respondents consisted of top managers, middle managers, lower managers, and employees of the internal and external Marketing Department of the Mandarin Oriental Hotel Jakarta, totaling 10 respondents. Before and during the Covid-19 Pandemic, the Mandarin Oriental Hotel Jakarta had implemented a Promotional Strategy to increase and maintain occupancy levels. Likewise, during the post-pandemic Covid-19 era, the Promotion Strategy was carried out, where advertising was carried out massively through digital platforms and third parties (digital media, bank promotion, and partnerships and the use of influencer marketing); Sales (Sales Promotion), modified according to the situation and conditions encountered; Personal Selling (Perjualan Personal), reactivated as an important strategy, apart from that brand awareness is influenced by government policies in terms of PPKM; Direct Marketing (Direct Marketing), carried out even though it is more enthusiastic but taking into account government policies in terms of PPKM; In terms of Public Relations, we always implement the we care program. This whole strategy involves all staff. The result is selling hotel products, creative thinking in developing certain activities, and increased employee loyalty.